Analysis of Early Reading Learning in Children with Intellectual Disabilities - Tri Sedya Silo Pratiwi; Arista Widyawati; Khofidotur Rofi’ah (Jurnal ORTOPEDAGOGIA, 2025)
This study is based on the fact that early reading learning is very important for children from an early age, including children with mild mental retardation. Children with mild mental retardation are those who experience intellectual disabilities that cannot be distinguished from children with severe mental retardation. Early reading learning must be carried out properly so that children with intellectual disabilities can follow the lessons well too. The purpose of this study was to determine how the process of early reading learning is carried out on children with mild mental retardation and whether the approach used is effective. Because children with mental retardation must be taught with methods that are appropriate to their conditions. This study is a descriptive study using a literature study method. The use of this method is in accordance with the objectives of the previous study. The results of the study indicate that several approaches and strategies can be used to help children with mild mental retardation learn to read early.